Clinical exome sequencing in neurogenetic and neuropsychiatric disorders - Fogel, Brent L. (Ann N Y Acad Sci, 2015)
Exome sequencing has recently been elevated to the standard of care for genetic diagnostic testing, particularly for genetically diverse and clinically heterogeneous disorders. This review provides a clinically oriented discussion of the next-generation sequencing technology that makes exome sequencing possible and how such technology is applied to the diagnosis of Mendelian disease, including clinically significant de novo variation, interpretation of variants of uncertain clinical significance, the future potential for genetic assessments of disease risk, and the substantial benefits in diagnostic efficiency. Important caveats are also discussed, including the implications of incidental or secondary findings detected during exome sequencing, and the relationship of exome sequencing to other methods of clinical genomic testing, such as chromosomal microarray and genome sequencing. Overall, the widespread adoption and use of exome sequencing in routine clinical practice is expected to improve diagnosis rates and reduce test costs, while leading to improvements in patient outcomes and a renewed emphasis on disease management.